2008
DOI: 10.1063/1.2908484
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Radio-Frequency Modules Test Facility Operating Experience

Abstract: Fermilab is heavily engaged and making strong technical contributions to the superconducting radio-frequency research and development program (SRF R&D). Four major SRF test areas are being constructed to enable vertical and horizontal cavity testing, as well as cryomodule testing. The existing Fermilab cryogenic infrastructure has been modified to service Fermilab SRF R&D needs. The first stage of the project has been successfully completed, which allows for distribution of cryogens for a single cavity cryomod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…At the time they were operating two Kinney skids, identical to the SNS skid, with their custom modifications. [3] Some of these modifications include new controls PLC hardware, new controls ladder logic including all necessary trip conditions, helium guard assembly for the roots blower shaft, and helium guard enclosures at both ends of the liquid ring pump.…”
Section: Introductionmentioning
confidence: 99%
“…At the time they were operating two Kinney skids, identical to the SNS skid, with their custom modifications. [3] Some of these modifications include new controls PLC hardware, new controls ladder logic including all necessary trip conditions, helium guard assembly for the roots blower shaft, and helium guard enclosures at both ends of the liquid ring pump.…”
Section: Introductionmentioning
confidence: 99%
“…Cryogenic fluids, including superfluid helium service, are provided by the Fermilab Meson area Cryogenic Test Facility [1,2]. This cryogenic system serves the ILC 1.3 GHz cavity Horizontal Test System (HTS) and the adjacent Spoke Resonator Test (SRT) 325 MHz cavity facility in the Meson Detector Building, and is capable of supporting simultaneous operation of both.…”
Section: Introductionmentioning
confidence: 99%
“…2 K operations at HTS are achieved, as previously described [2], by large capacity standard rotary vacuum pump handling very low pressure helium gas at room temperature. The system has demonstrated that it can deliver continuous and reliable subatmospheric operation for closed-loop production of superfluid helium for SRF cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Fermi National Accelerator Laboratory is constructing a superconducting radiofrequency (RF) test facility located at the New Muon Lab building at Fermilab for testing 1 the performance of superconducting radio frequency cavities in a cryomodule (CM). A multi-phased approach is being taken at the facility beginning with the installation and testing of the Capture Cavity II (CC2), a single high-gradient 1.3 GHz 9-cell superconducting RF cavity installed in a cryomodule cryostat.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-phased approach is being taken at the facility beginning with the installation and testing of the Capture Cavity II (CC2), a single high-gradient 1.3 GHz 9-cell superconducting RF cavity installed in a cryomodule cryostat. This cavity was previously installed at the Fermilab MDB test facility where it operated for several years [1]. This initial phase will allow for commissioning of the cryogenic distribution system leading to the test cave as well as allow for full RF testing and commissioning.…”
Section: Introductionmentioning
confidence: 99%